Influence of shock waves and muscle activity at initial contact on walk-run Transition evaluated by two models - Shung, K.; de Oliveira, C. G.; Nadal, J. (Journal of Applied Biomechanics, 2009)
The walk-run transition (WRT) is a well-described phenomenon without any known cause; however, mechanical variables related to human gait have been associated with the WRT. This study tested the hypothesis that shock waves in the tibia and 3rd lumbar vertebra in addition to activity of tibialis anterior, vastus lateralis, and erector spinae muscles could be responsible for the WRT. Thirty subjects walked and ran on a treadmill at 80%, 90%, 100%, 110%, and 120% of preferred transition speed. Shock waves were measured with skin-mounted accelerometers and muscle activity by surface electromyography. The influence on the WRT was analyzed with two models. The shock waves and muscle activity tended to a significant increase (p < .05) for both walking and running with increased speed. The only factor that appeared to be involved in the WRT mechanism was the activity of the tibialis anterior; however, this was only confirmed by one of the two models. The use of different models to analyze the same data for the WRT triggers may give different results; thus, a standard model is required to investigate the influence of given factors on biological phenomena.